Przedsiębiorstwo jako przedmiot czynności prawnych spory doktrynalne z perspektywy praktyki obrotu: [Enterprise as a subject of acts in law - doctrinal disputes from the perspective of commercial practice] (Studia Prawnicze / The Legal Studies, 2009)
Przedsiębiorstwo w znaczeniu przedmiotowym (art. 551 k.c.)1ma skomplikowaną naturę. Sprzyja to powstawaniu rozmaitych perturbacji na poziomie legislacyjnym i wykładniczym, a w ślad za tym w praktyce obrotu. Śmiało można powiedzieć, iż problematyka ta wykazuje swoiste Janusowe oblicze. Dla teoretyków stanowa źródło wyzwań intelektualnych oraz wdzięczne pole do formułowania różnorodnych koncepcji i poglądów prawnych, zgłaszania rozmaitych propozycji rozwiązań i toczenia polemik doktrynalnych. Jednakże to, co stanowi inspirację dla badaczy, staje się poważną bolączką dla praktyków - nie dość bowiem, że transakcje mające za przedmiot przedsiębiorstwo są ze swej natury trudne, to w dodatku zadania polegającego na prawidłowymdoradztwie prawnym nie ułatwiają liczne w tym wypadku kontrowersje teoretyczne. Legal issues of the enterprise have been for a long time the object of numerous and serious doctrinal and judicatory controversies. They influence negatively the practice of legal transactions, causing legal uncertainty and, what follows, unpredictability of the judicatory organs’ stand. Transactional risk, increased as a result of that state of affairs, discourages the conducting of legal actions whose object is an enterprise and induces the use of substitute legal forms, such as e.g. the purchase of stocks or shares in companies or the partition of companies. The analysis of the literature and judicature’s current views (strongly differentiated, dispersed in fact) has brought the author to the conviction that only some of the issues considered controversial have indeed substantiated bases. She has also observed that the problems raised have issued not infrequently from the lack of a sufficiently systematic approach to the subject under analysis. The above mentioned observations have led the author to a recapitulation of doctrinal and judicatory discussions while simultaneously systematizing and organizing the hitherto reported legal views, as well as explaining reasons and sources of the controversies revealed. The assumption, adopted as the "key", according to which the solving of principal problems determines the content of solutions in more detailed issues, allowed formulating conclusions which ought to bring effect in the shape of at least a partial agreement or only a rapprochement of stands. The present work consists actually of two layers. One of them is devoted to the discussion of the legal issues of the enterprise and to the critical analysis of the state of doctrinal and judicatory decisions in that matter. Against that background, and at the same time within the second current of her considerations, the author shares her observations on the method of cultivating the dogmatics of civil law.